Inovasi Teknologi Media Sosial: Keberhasilan Proses Adopsi Meningkatkan Kelincahan Organisasi - Kosasi, Sandy (E-Proceedings KNS&I STIKOM Bali; 2017, 2017)
This paper discussed the model of business digital with the capabilities to adopt the technological innovation of social media and to optimize the resources to improve the performance agility of business organizations. Competitiveness needs speed and innovation in responding to the exploitation of organizational improvement and benefit. This research applied a qualitative descriptive and explanatory method and referred to a number of previous studies concerning adoption, social media, and organizational agility. This research aimed to explore how far the adoption of technological innovation of social media in contributing to the formulation for the improvement of organizational performance agility and to the identification of factors ensuring the implementation success. The result showed that the adoption of technological innovation of social media affect in improving the agility of small and medium organizations. Organizations possessing agility can adapt every change quickly. The adoption success becoming the basis of digital marketing strategies depends on technology, organizations, and environment. Awareness and willingness are also determiners. Digitization makes organizations more agile in adapting the competitiveness.